Effects of changing a module's interface: a case study in an automotive company. (23rd January 2007) - Persson, Magnus
Product modularisation strategy is used to achieve products consisting of completely decoupled modules. This enables one module to be changed without affecting the others. The present paper concerns a case study done at a car manufacturing company, which made a change in one of its modules that made it less decoupled. Large differences were found between some of the estimated effects and the actual ones, indicating the importance of making holistic evaluations of the changes before they are carried out. This clarifies the risks of altering a module's interface for less decoupling without a thorough analysis of the consequences.